ANALISIS PENGADAAN HELIKOPTER ESCORT UNTUK MENDUKUNG OPERATIONAL READY FORCE TNI ANGKATAN LAUT - Iwan Purwanto; Ranu Samiaji; H. Lestianto (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The geographical condition of Indonesia, which consists of tens of thousands of islands, makes the potential threat to be even greater at any time, so that the readiness of the Navy in implementing Military Operations is a necessity. Amphibious operations are part of the Military Operations, which is essentially an operation in integrating various types of forces, namely ships, aircraft and landing troops in an attack on the enemy's coast and/or potentially controlled by the enemy and is marine in nature in the sense that the Navy plays a major role as which is reflected in the implementation of the operation. Faced with the functions and duties of Naval Aviation, currently the Indonesian Navy in general and Puspenerbal in particular do not yet have special combat helicopters to carry out escorts in support of amphibious operations. The selection of the Escort Helicopter can be carried out in an integrated manner using the Integrated Performance Measurement System, DEMATEL, ANP methods. This research is expected to provide advice and input to the leadership of the Indonesian Navy in procurement an escort helicopter that is strategically objective. In carrying out calculations and data processing, the results obtained are taking the Amphibious Operations Test (O1) sub-criteria, which is the most dominant strategic target in the prominance criteria group with a value of 6.9 which is slightly adrift with the budget sub-criteria (PR2) with a value of 6 ,89. In general, the Amphibious operation criteria are the most dominant compared to other criteria because they rank 1, 3 and 4. Furthermore, the Escort Helicopter Procurement budget sub-criteria is the item that has the largest weight which greatly affects so that it must be guarded not to drop because it can affect the overall weight assessment.